Estimates of the Best M-Term Trigonometric Approximations of the Classes L_β, p^ψ of Periodic Functions of Many Variables in the Space L_q - Konsevich, N. M. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain order estimates for the best trigonometric approximations of the classes L_β, p^ψ of periodic functions of many variables in the spaceL_q for 1 < p < q ≤ 2 and 1 < q ≤ p < ∞.